Computer simulation of simple and complex electrolyte solutions - Khurshid, Farhat (Kansas State University, 2024)
The computer simulation of simple and complex electrolyte solutions is a powerful tool for understanding the behavior of ions in various environments, ranging from fundamental studies to practical applications. In these simulations, computational models mimic the behavior of ions in solution by considering their interactions with solvent molecules and other ions. Classical molecular dynamics simulations are often used for simple electrolyte solutions. These simulations provide insights into ion solvation, pairing, etc. In contrast, simulating complex electrolyte solutions, such as seawater, requires more effort. By elucidating the microscopic details of electrolyte solutions, computer simulations can aid in the design of new materials, the optimization of industrial processes, and provide fundamental advances in fields as diverse as electrochemistry, geochemistry, and biophysics. This thesis is divided into two main parts. The first part involves the simulation of simple ionic solutions and the development of a classical force field for alkali metal nitrate and alkaline earth nitrate aqueous solutions. We adjust the charges on N and O atoms of the nitrate ion, along with Lennard-Jones parameters (σ and ϵ) to optimize the model. We then test the parameters by determining Kirkwood-Buff Integrals (KBIs) for a series of alkali and alkaline earth metal nitrates at various concentrations in water and comparing them to their experimental KBIs. Good agreement between the simulated and experimental KBIs was observed. The second part of the thesis deals with more complex electrolyte solutions. We simulate 2 M pure alkali chloride aqueous solutions, together with mixtures of two 1 M alkali chloride aqueous solutions, both placed between Au plates. The Au layers were either charged or uncharged. We could identify the preference of the different alkali metal ions for the charged Au plates that varies with the charge on the plates. The two main competing factors were the loss of the solvation shell and the effect of ion pair formation in the bulk solution. We also simulated a second set of complex electrolyte solutions. We compare and contrast the properties of regular seawater, red sea water, and dead sea water using a Kirkwood Buff theory approach. This was achieved by separating the KBIs into thermodynamic and charge neutralization contributions, which represents a new approach for the comparison of electrolyte solutions.
Keywords: Molecular dynamics; Ionic solutions; Force field; Electrolytes; Mixed electrolytes